Legal protection for children in armed conflict - Miloud AbdAljallil Mentfah (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Wars are as old as humanity, and are still up to the present time, with the development taking place in weapons, techniques of war and destruction, the most severe effects of these wars on children are due to their helplessness, and despite the available legal texts aimed at ensuring their protection However, this still did not reach the required level, and child victims in wars account for the majority of losses and the most important of all. They affect, at present and in the future, human aspirations towards a better life, and the research tries to consider the legal protection available to children in times of wars and armed conflicts.